Anticipated delay in help-seeking for cancer symptoms: Findings from a nationwide study of Malaysian adults. (April 2021) - Schliemann, Désirée; Ismail, Roshidi; Donnelly, Michael; Su, Tin Tin
Highlights: First nationwide study on anticipated help-seeking for cancer signs in Malaysia. Data was collected from adults living across all states of Malaysia. Low anticipated delay to help seeking compared to other countries. Living in a disadvantaged community was associated with anticipated delay >2 weeks. Abstract: Background: To investigate the relationship between anticipated delay in help-seeking and cancer symptom recognition and the extent to which this relationship varied according to socio-demographic and health-related characteristics. Methods: A cross-sectional telephone survey was conducted of 1895 adults aged ≥40 years who were randomly selected across Malaysia and interviewed using the Awareness and Beliefs about Cancer questionnaire, which was previously validated and culturally adapted by the research team. Logistic regression analysis was used to test the associations between anticipated delay for help seeking >2 weeks and socio-demographic and health-related variables. Results: Anticipated delay in help-seeking was reported for persistent cough (19.3 %), rectal bleeding (6.1 %) and breast changes (2.5 %). Difficulty in accessing a doctor was associated with anticipated delayed help-seeking for breast changes and rectal bleeding (adjusted ORs 7.58; 95 % CI 1.98, 28.94 and 2.37; 95 % CI 1.21, 4.66, respectively); not recognising the symptom 'unexplained bleeding' as a colorectal cancer warning sign was associated with anticipated delayed help-seeking for rectal bleeding (adjusted OR 1.54; 95 % CI 1.03, 2.31); and ethnicity was associated with anticipated delay for rectal bleeding and persistent cough. Conclusions: Generally, anticipated delay to help-seeking for cancer symptoms in Malaysia (a middle-income country) appeared to be a less significant problem compared to other countries including high-income countries. There appeared to be a significant association between social variation indicators in Malaysia and anticipated delay in help-seeking.